Temperature Frequency Characteristics of Charge Transition in the Li0.5Fe2.4Ti0.1O4 Non-stoichiometric System - Gasyuk, I.M.; Ugorchuk, V.V.; Kaykan, L.S.; Deputat, B.J. (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
A study of conductivity temperature frequency dependence of Li0.5Fe2.4Ti0.1O4 non-stoichiometric spinel has exhibited frequency dispersion conductivity presence. The time of relaxation (τ) proved to make 2·10-6s within the limits of dispersion. The conductivity size was found to be dependant upon the amount of Fe2+ ions in the structure.